Results of Treatment of Hypertriglyceridemia-induced Acute Necrotizing Pancreatitis with the Use of Plasmapheresis - Shevchuk, Igor; Kuzenko, Roman; Pylypchuk, Volodymyr; Нalipchak, Igor; Gedzuk, Sergiy; Snizhko, Sergiy (Acta medica Lituanica, 2026)
Introduction: Additional risk factors have been identified, and the outcomes of surgical treatment in patients with hypertriglyceridemia-induced acute necrotizing pancreatitis treated with plasmapheresis have been analyzed.Aim: To evaluate the effectiveness of plasmapheresis in the treatment of patients with hypertriglyceridemia-induced acute necrotizing pancreatitis, with an emphasis on the early use of minimally invasive techniques and delayed open surgical interventions, and to identify additional risk factors associated with adverse disease outcomes.Materials and methods: The treatment outcomes of 82 patients have been analyzed: 53 patients (65%) were included in the main group, and 29 patients (35%) were included in the comparison group.Results: The use of plasmapheresis resulted in a significant reduction in blood triglyceride levels (p=0.002), total cholesterol (p=0.001), low-density lipoproteins (p=0.012), and the atherogenic index (p=0.001). In the comparison group, the decrease in these parameters was not significant. In the main group, a favorable disease course and the effectiveness of minimally invasive interventions were achieved in 60% of the patients (29/48), compared with 46% (12/26) in the comparison group (p=0.238).Discussion: According to the ROC analysis, adverse prognostic factors for a complicated disease course included arterial hypertension (p=0.042), overweight with a body mass index greater than 27.6 kg/m² (p=0.030), diabetes mellitus (p=0.021), and hypertriglyceridemia (p=0.001). This study will allow us to evaluate the results of the treatment of patients with hypertriglyceride-induced acute necrotic pancreatitis and the effectiveness of plasmapheresis, as well as to identify additional prognostic risk factors leading to laparotomy.Conclusions: Plasmapheresis in the early stages of hypertriglyceride-induced acute necrotic pancreatitis had a positive effect on the course of the disease and ensured the final effectiveness of mini-invasive surgical interventions in 60% of the patients in the main group. Additional prognostic factors for complicated hypertriglyceride-induced acute necrotic pancreatitis, accompanied by purulent-septic complications and requiring laparotomy, are arterial hypertension, a body mass index greater than 27.6 (kg/m2), diabetes mellitus, and hypertriglyceridemia.
Keywords: hypertriglyceridemia; acute necrotizing pancreatitis; plasmapheresis; laparotomy risk factors; surgical treatment